Parental reassurance concerning a feverish child: determinant factors in rural general practice - Anthony Chapron (BMC Family Practice, 2018)
Abstract Background Acute fever is the most common pediatric condition encountered in general practice and a source of parental concern that can result in inappropriate behavior. The main objective of this study was to describe and quantify parental reassurance concerning their feverish child in the context of visits to rural general practitioners (GPs). Method The study included the parents of 202 feverish children, aged from 3 months to 6 years, consulting 13 representative rural GPs. Questionnaires were administered before and after the consultation. Uni- and multivariate analysis were performed to study variations of the levels of concern and associated factors. Results The duration of fever was 1.3 days (± 1.1). The mean score for parental concern was 4.8 out of 10 (± 2.2) before, and 2.4 (± 1.9) after the consultation (p < 0.0001). The concern correlated with the timing of the appointment relative to the usual wait (p = 0.0002), and a lack of knowledge about fever complications (p = 0.013). Conclusion Facilitating access to consultations with a GP within the expected timeframe reduces parental concern. Increasing parental education about fever is also necessary.